Sistema web para el control de inventario del área de gabinete en el proyecto del museo de sitio de Túcume-Lambayeque - Purisaca Martinez, Gerson Moises (2019)
The investigation entitled "WEB SYSTEM FOR INVENTORY CONTROL OF CABINET AREA IN THE PROJECT OF THE TUCUME-LAMBAYEQUE SITE MUSEUM" has as main objective to demonstrate that through the application of development technologies and agile methodologies it can be improved; streamlining the processes of control, registration and traceability of archaeological materials during excavation projects. The study was developed on the project called "ARCHAEOLOGICAL RESEARCH, CONSERVATION AND RESTORATION-DIFFUSION, SENSITIZATION AND CULTURAL STRENGTHENING OF THE PIP" RECOVERY OF HUACA LOS GAVILANES, LOS GAVILANES CEMETERY, HUACA LAS ABEJAS AND HUACA FACHO OF THE SOUTHWEST SECTOR OF THE ARCHAEOLOGICAL COMPLEX OF TÚCUME, DISTRICT OF TÚCUME, PROVINCE AND DEPARTMENT OF LAMBAYEQUE ", STAGE 2018" analyzing the chain of process that compose and interact with the cabinet area, later proceeded to the development of the project, using techniques for the development of software such as CRC cards, and the SCRUM methodology. It was proposed to systematize the main processes of the cabinet area, so that there is a more automated control of the amount of archaeological material found daily, activities such as: • Efficiently control the entry of materials. • Make inquiries easily and transparently • Prepare reports immediately The main achievement has been to improve different processes in the cabinet area, described in the objectives of this thesis, which will allow future projects to have a much greater advance in the processing of information collected in the field, and at the management level of the materials depending on the approach that the project managers can give to this developed tool.